2008
DOI: 10.1002/hep.22317
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor induces proliferation of hepatic progenitors in alcoholic steatohepatitis: A randomized trial

Abstract: Liver failure is the major cause of death in alcoholic steatohepatitis (ASH). In experimental hepatitis, granulocyte-colony stimulating factor (G-CSF) mobilizes hematopoietic stem cells, induces liver regeneration, and improves survival. We studied the short-term effects of G-CSF on CD34؉ stem cell mobilization, liver cell proliferation, and liver function in patients with ASH. Twenty-four patients (mean age 54 years) with alcoholic cirrhosis [Child-Turcotte-Pugh score 10 (7-12)] and concomitant biopsy-proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(162 citation statements)
references
References 29 publications
5
148
0
6
Order By: Relevance
“…Furthermore, several routes of cell administration have been investigated, included peripheral veins, the hepatic artery, and the portal vein [45][46][47][48][49][50][51][52][53][54]. In a randomized control study, Spahr et al reported that there were no significant differences in treatment outcomes when using autologous BMNCs harvested after G-CSF infusion through the hepatic artery, although several other randomized studies have shown favorable results, suggesting the usefulness of these therapies [50]. More recently, the Repeated AutoLogous Infusion of Stem cells In Cirrhosis (REALISTIC), a multicenter, phase II, open-label, randomized controlled trial of repeated autologous infusion of G-CSF-mobilized CD133?…”
Section: Autologous Bone Marrow Cell Injection Therapy and Related Trmentioning
confidence: 99%
“…Furthermore, several routes of cell administration have been investigated, included peripheral veins, the hepatic artery, and the portal vein [45][46][47][48][49][50][51][52][53][54]. In a randomized control study, Spahr et al reported that there were no significant differences in treatment outcomes when using autologous BMNCs harvested after G-CSF infusion through the hepatic artery, although several other randomized studies have shown favorable results, suggesting the usefulness of these therapies [50]. More recently, the Repeated AutoLogous Infusion of Stem cells In Cirrhosis (REALISTIC), a multicenter, phase II, open-label, randomized controlled trial of repeated autologous infusion of G-CSF-mobilized CD133?…”
Section: Autologous Bone Marrow Cell Injection Therapy and Related Trmentioning
confidence: 99%
“…Transplanted oval cells can make a modest (∼2% after 1 month, falling to 0.4% at 6 months) contribution to the hepatocyte population in the CCl 4 -damaged mouse liver [92]. The progenitor response can be manipulated in vivo; in the 2-AAF/PH model the oval cell reaction can be significantly boosted by G-CSF [93], and a small study of patients with alcoholic steatohepatitis found that 5 days of G-CSF treatment resulted in a four-fold increase in proliferating HPCs [94].…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitor mentioning
confidence: 99%
“…Whereas transplantation of HPCs has been successful in rodents (9), isolation of human HPCs is not a practical therapeutic option (10). Manipulation of the liver's endogenous DRs and HPCs represents a more realistic therapeutic approach (11,12).…”
mentioning
confidence: 99%